2012
DOI: 10.1007/s11103-012-9887-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Darjeeling tea flavour on a molecular basis

Abstract: Darjeeling teas are the highest grown teas in the world and preferred for its flavour, aroma and quality. Apart from the genetic makeup of the plant, earlier reports suggest that insect infestation, particularly jassids and thrips triggers the aroma and flavour formation in Darjeeling tea. The present work encompasses the identification of the genes/transcriptomes responsible for the typical flavour of Darjeeling tea, besides understanding the role of jassids and thrips in particular, in producing the best cup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…1B). Transcriptomic analysis revealed that enhanced flavour (aroma) due to altered expression levels of the genes in the corresponding pathways occurs in some tea cultivars or results from insect infestation of fresh leaves (Gohain et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1B). Transcriptomic analysis revealed that enhanced flavour (aroma) due to altered expression levels of the genes in the corresponding pathways occurs in some tea cultivars or results from insect infestation of fresh leaves (Gohain et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Loivamäki et al (2004) also reported that jasmonate induction led to an increase in tobacco alkaloids, phenolics, and diterpene glycosides in Nicotiana attenuate. Moreover, the impacts of MeJA on the biosynthesis of volatile compounds in climacteric and non-climacteric fruits, such as apples and strawberries, respectively, have also been reported (Ayala-Zavala et al, 2005;Kim et al, 2006;de la Peña Moreno et al, 2010a;2010b;Belhadj et al, 2008;Gohain et al, 2012). However, investigations toward the effects of exogenous MeJA on tea aroma have been scarcely reported.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the raw Cp values of all the reference genes are transformed into relative quantities using ΔΔCt method [25]. For relative quantification assays, the expression of the target gene is expressed as ratio of target-to-reference gene in the same sample.…”
Section: Relative Gene Expression (Qrt-pcr) Analysis Of the Enzymes Imentioning
confidence: 99%